Recommendations for the pharmacological management of neuropathic pain: an overview and literature update - Dworkin, Robert H.; O'Connor, Alec B.; Audette, Joseph; Baron, Ralf; Gourlay, Geoffrey K.; Haanpää, Maija L.; Kent, Joel L.; Krane, Elliot J.; LeBel, Alyssa A.; Levy, Robert M.; Mackey, Sean C.; Mayer, John; et al. (Mayo Clinic proceedings, 2010)
The Neuropathic Pain Special Interest Group of the International Association for the Study of Pain recently sponsored the development of evidence-based guidelines for the pharmacological treatment of neuropathic pain. Tricyclic antidepressants, dual reuptake inhibitors of serotonin and norepinephrine, calcium channel α2-δ ligands (ie, gabapentin and pregabalin), and topical lidocaine were recommended as first-line treatment options on the basis of the results of randomized clinical trials. Opioid analgesics and tramadol were recommended as second-line treatments that can be considered for first-line use in certain clinical circumstances. Results of several recent clinical trials have become available since the development of these guidelines. These studies have examined botulinum toxin, high-concentration capsaicin patch, lacosamide, selective serotonin reuptake inhibitors, and combination therapies in various neuropathic pain conditions. The increasing number of negative clinical trials of pharmacological treatments for neuropathic pain and ambiguities in the interpretation of these negative trials must also be considered in developing treatment guidelines. The objectives of the current article are to review the Neuropathic Pain Special Interest Group guidelines for the pharmacological management of neuropathic pain and to provide a brief overview of these recent studies.
Available online 20 October 2011
Gesehen am 15.05.2023